2013
DOI: 10.1155/2013/242450
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Abrasive Wear Behavior of Metal Sulphide Lubricant Filled Epoxy Composites

Abstract: The present work reveals the effect of the addition of commercial MoS 2 (10 wt%) particles on mechanical and two-body abrasive wear behavior of epoxy with/without glass fiber mat reinforcement. The composites were fabricated using casting and simple hand lay-up techniques followed by compression molding. The mechanical properties such as density, hardness, tensile, and flexural properties were determined as per ASTM standards. The abrasive wear testing was carried out using pin-on-disc wear tester for differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Sudheer et al. 26 was also reported the similar trend of increase in density values by increasing content of molybdenum disulphide to glass fibre-epoxy matrix.
Figure 3.Percentage of C30B (wt.
…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Sudheer et al. 26 was also reported the similar trend of increase in density values by increasing content of molybdenum disulphide to glass fibre-epoxy matrix.
Figure 3.Percentage of C30B (wt.
…”
Section: Resultsmentioning
confidence: 52%
“…% PP/C30B/EA nanocomposite due to the presence of more amount of C30B when compared to the other combination of PP/C30B/EA nanocomposite specimens. Sudheer et al 26 was also reported the similar trend of increase in density values by increasing content of molybdenum disulphide to glass fibre-epoxy matrix.…”
Section: Density Of Pp/c30b/ea Nanocompositesmentioning
confidence: 52%
“…The versatility of the inorganic ller in improving the exural strength reduces beyond the crucial addition of y ash because of the accumulation of inorganic llers (Shivamurthy et al, 2013;Taurozzi et al, 2012). This ller accumulation is affected by an increment of ller-ller interactions during the mechanical stirring process (Sudheer et al, 2013). The llers accumulation would potentially increment polymer-ller interruption viscosity and affect bad wetting reaction between them (Sudheer et al, 2013).…”
Section: Flexural Propertiesmentioning
confidence: 99%
“…This ller accumulation is affected by an increment of ller-ller interactions during the mechanical stirring process (Sudheer et al, 2013). The llers accumulation would potentially increment polymer-ller interruption viscosity and affect bad wetting reaction between them (Sudheer et al, 2013). Hence, the lower enhancement in the exural characteristics was endorsed for CFTIPE that signi es 65% improvement compared to a neat epoxy polymer.…”
Section: Flexural Propertiesmentioning
confidence: 99%
“…There is much research on the friction and wear of epoxy resin filled with SiC or MoS 2 [ 20 , 21 , 22 , 23 , 24 ], but, so far, there are few reports on the synergistic filling of SiC and MoS 2 . In this paper, EP composites with different proportions of SiC and MoS 2 were prepared.…”
Section: Introductionmentioning
confidence: 99%